Innovation toolkit for identification of the optimal module options in open platform architecture products - Sikhwal,RK; Childs,PRN (Design Society, 2018)
Open platform architecture products (OPAP) are the keyenablers for Product designfor Mass Individualisation.Itis a new product design paradigm that comprises an open hardware platform, mass-producedby large manufacturersand multiple independent modules,invented and produced by other smaller companies and by the end-userthat are integratedwith the platform. It gives freedom to end-usersto integrate different modules into the platform as per their choice. This type of product integration will be engaged with by the all actors involved in the design and aims to help them to be more creative and innovative. The end product will be highly individualised and technologically advanced.Based on explorative literature analysis, with practical insights from an industrial questionnaire survey, anInnovation toolkitfor the end-userhas beendeveloped.TheInnovation toolkitprovides a mean of selecting an optimal module option for each module which will be integrated onthe hardware platform. The design of theInnovation toolkitfor OPAP has been approachedin three different steps: Modelling of OPAP, Modelling of evaluation measures and evaluation indices with end-userpreferences and Identification of the optimal module options. In this work, variations in module options for a given module are modelledby an AND-OR tree and parameters of the nodes in this tree. Different module options for the selected module are evaluated by various evaluation measures. These evaluation measures are convertedinto comparable customer satisfaction indices. The optimal OPAP is identifiedby constrained optimisationof the overall customer satisfaction index. Twocase studieshavebeen presented to demonstrate theeffectiveness of the introduced Innovation toolkit.These case studies illustrate that the Innovation toolkit can readily be appliedto these typesof product developmentto obtain a highly individualised OPAP with optimised mo